Lokanāyaka Aṇe va tyāñcā kāḷa : Padmavibhūsha.na lokanāyaka Mādhava Śrīhari upākhya Bāpūjī Aṇe yāñce caritra - Haradāsa, Vīṇā, 1929- (Lokanāyaka Aṇe Janmaśatābdī Samiti, 1982)
Biography of Madhao Shrihari Aney, 1880-1968, social activist and Indian freedom fighter.